Safety and efficacy of human Wharton's Jelly-derived mesenchymal stem cells therapy for retinal degeneration - Leow, S. N.; Luu, Chi D.; Hairul Nizam, M. H.; Mok, Pooi Ling; Ruhaslizan, R.; Wong, H. S.; Wan Abdul Halim, Wan Haslina; Ng, M. H.; Ruszymah, B. H. I.; Chowdhury, S. R.; Bastion, M. L. C.; Then, K. Y. (Public Library of Science, 2015)
Purpose To investigate the safety and efficacy of subretinal injection of human Wharton’s Jelly-derived mesenchymal stem cells (hWJ-MSCs) on retinal structure and function in Royal College of Surgeons (RCS) rats.